Identical or fraternal twins? The chemical homogeneity of wide binaries from Gaia DR2. Issue 1 (10th January 2020) - Hawkins, Keith; Lucey, Madeline; Ting, Yuan-Sen; Ji, Alexander; Katzberg, Dustin; Thompson, Megan; El-Badry, Kareem; Teske, Johanna; Nelson, Tyler; Carrillo, Andreia
ABSTRACT: One of the high-level goals of Galactic archaeology is chemical tagging of stars across the Milky Way to piece together its assembly history. For this to work, stars born together must be uniquely chemically homogeneous. Wide binary systems are an important laboratory to test this underlying assumption. Here, we present the detailed chemical abundance patterns of 50 stars across 25 wide binary systems comprised of main-sequence stars of similar spectral type identified in Gaia DR2 with the aim of quantifying their level of chemical homogeneity. Using high-resolution spectra obtained with McDonald Observatory, we derive stellar atmospheric parameters and precise detailed chemical abundances for light/odd-Z (Li, C, Na, Al, Sc, V, Cu), α (Mg, Si, Ca), Fe-peak (Ti, Cr, Mn, Fe, Co, Ni, Zn), and neutron capture (Sr, Y, Zr, Ba, La, Nd, Eu) elements. Results indicate that 80 per cent (20 pairs) of the systems are homogeneous in [Fe/H] at levels below 0.02 dex. These systems are also chemically homogeneous in all elemental abundances studied, with offsets and dispersions consistent with measurement uncertainties. We also find that wide binary systems are far more chemically homogeneous than random pairings of field stars of similar spectral type. These results indicate that wide binary systems tend to be chemically homogeneous but in some cases they can differ in their detailed elemental abundances at a level of [X/H] ∼ 0.10 dex, overall implying chemical tagging in broad strokes can work.